Mortality Statistics from National Censuses: A Low Cost Viable Method - Fric, A; Kandel, N; Singh, N (Journal of Nepal Health Research Council, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Information related to mortality is pivotal for evidence based policy and planning, resource mobilization and impact of intervention. This information is essential to monitor trends in health situation of the population, detect new epidemics, encourage research into avoidable causes of death, evaluate the success of control programs, and improve accountability for expenditures on disease control. Sixty percent of the countries of the world donâ€™t provide enough information on vital events and complete and representative information. Apart from vital registration system, other methods for getting mortality data are in current practices, such as facility based information system, censuses,Â household survey, research demographic surveillance sites, epidemiological studies and sample vital registration system, which complement the national health information system. All methods have their limitations. Piggy backing of national censuses for mortality statistics would follow the principle of Sample Registration System (SRS) using verbal autopsy tools to generate the mortality data just after the censuses. This method can be the suitable/useful mortality measuring system representing the population by age, sex, location and causes of death with less effort and at a lower cost. This method can be used to verify mortality data collected from other sources and/or for adjustment of existing mortality data. Key words: epidemics, epidemiological studies, sample registration system, surveillance, survey